Mga siniping gintong kaisipan ni Dr. Jose P. Laurel - Laurel, Jose P. (Jose Paciano) 1891-1959 (Celia Diaz-Laurel, 2012)
Selected quotes from Dr. Jose P. Laurel's articles and speeches during his presidency.